2022
DOI: 10.1186/s12302-022-00605-3
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role of microplastics in the etiology of lung ground glass nodules

Abstract: Background Microplastic pollution has become a serious global environmental threat. The abundance of microplastics in the air is an order of magnitude higher than that in other media, which means that all living animals breathing with lungs (including humans) cannot escape the fate of inhaling microplastics. However, there is no direct evidence to demonstrate what type and abundance of microplastics exist in lung tissue. In addition, whether the retention of microplastics and the long-term fric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…Whilst there is a small chance that these particles were inhaled from the environment, one would expect to see a greater abundance of smaller MP for the anatomical regions studied and hence more data is needed to draw conclusions from these observations. Additionally, in situ analyses, such as via spectral imaging, will strengthen this, such as the method applied by Chen et al ( 28 ) which detected a cellulose fiber in a lung tumor tissue section.…”
Section: Microplastic Inhalation Exposurementioning
confidence: 98%
See 1 more Smart Citation
“…Whilst there is a small chance that these particles were inhaled from the environment, one would expect to see a greater abundance of smaller MP for the anatomical regions studied and hence more data is needed to draw conclusions from these observations. Additionally, in situ analyses, such as via spectral imaging, will strengthen this, such as the method applied by Chen et al ( 28 ) which detected a cellulose fiber in a lung tumor tissue section.…”
Section: Microplastic Inhalation Exposurementioning
confidence: 98%
“…Few studies explicitly estimate exposure. Chen et al ( 28 ) estimate nail salon employees to be exposed to 260 MPs per day. However, if inhaled, these particles are likely to deposit in the upper airways and be swallowed due to the particle sizes being >25 μm.…”
Section: Microplastic Inhalation Exposurementioning
confidence: 99%
“…In ground glass nodules (GGN) (lesions in human lungs), cotton, rayon, and microplastic fibers (>20 m) were found in a larger fraction of the lesions than in lung tissue. 85 The incidence of microplastic-containing GGN correlated positively to age and to the detection of cancer. The microfibers were more degraded in GGN than in lung tissue; rougher fibers may either be more toxic or immunogenic themselves or may release toxic chemicals into the surrounding tissue.…”
Section: Substance Class Distribution Of Total Registered Substances ...mentioning
confidence: 99%
“…Only the former two exposure routes can cause actual MF intake. Inhalation of MFs can adversely affect the respiratory tracts (Lim et al 2021 ; Moolgavkar et al 2001 ), which has also been suggested to be associated with the formation of ground glass nodules in human lungs (Chen et al 2022 ). Ingestion of MFs has been confirmed in various organisms, including aquatic organisms (fish, decapods, bivalves, zooplankton, etc.…”
Section: Exposure and Health Risksmentioning
confidence: 99%